The State of Corporate Governance Research - Bebchuk, Lucian A.; Weisbach, Michael S. (Review of Financial Studies, 2010)
This article, which introduces the special issue on corporate governance cosponsored by the Review of Financial Studies and the National Bureau of Economic Research (NBER), reviews and comments on the state of corporate governance research. The special issue features seven articles on corporate governance that were presented in a meeting of the NBER’s corporate governance project. Each of the articles represents state-of-the-art research in an important area of corporate governance research. For each of these areas, we discuss the importance of the area and the questions it focuses on, how the article in the special issue makes a significant contribution to this area, and what we do and do not know about the area. We discuss in turn work on shareholders and shareholder activism, directors, executives and their compensation, controlling shareholders, comparative corporate governance, cross-border investments in global capital markets, and the political economy of corporate governance.